Tables of nutrient allowances for cattle based on brazilian research data - Miranda, Roberto Meirelles de; Gama, Maurício Pinho da (Pesquisa Agropecuaria Brasileira, 2014)
Tables of nutrient allowances were computed based on data taken from 53 cattle feeding experiments made in tropical Brazil. Multiple correlations and regressions having DM, CP and TDN consumption as dependent variables and live weight and daily gain as independent variables were highly significant (P<0.10) and served to compute the new tables. These show higher consumptions of DM, CP and TDN than NRC tables, reflecting differences in cattle, rations and management conditions in Brazil. The tables give the first approximation of nutrient allowances for purebred and grade zebu cattle fed in confinement, under Brazilian conditions.